Analytical and stochastic modeling techniques and applications : 23rd International Conference, ASMTA 2016, Cardiff, Wales, August 24-26, 2016. Proceedings /: 23rd International Conference, ASMTA 2016, Cardiff, Wales, August 24-26, 2016. Proceedings. (2016) - Unknown
No abstract available